Statistics for business and economics - Newbold, Paul (Pearson Education, 2022)
Statistics for Business and Economics enables readers to conduct serious analysis of applied problems rather than running simple “canned” applications. This text is at a mathematically higher level than most business statistics books and provides readers with the knowledge they need to become stronger analysts for future managerial positions. The 10th edition has been revised and updated to improve problem contexts and demonstrate how statistical methods enhance understanding of business and economics.